Safety and efficacy of once-weekly basal insulin Fc in people with type 2 diabetes previously treated with basal insulin: a multicentre, open-label, randomised, phase 2 study. Issue 3 (March 2023) - Frias, Juan; Chien, Jenny; Zhang, Qianyi; Chigutsa, Emmanuel; Landschulz, William; Syring, Kristen; Wullenweber, Paula; Haupt, Axel; Kazda, Christof
Summary: Background: The burden of daily basal insulins often causes hesitancy and delays in the initiation of insulin therapy. Basal insulin Fc (BIF, insulin efsitora alfa), designed for once-weekly administration, is a fusion protein combining a novel single-chain insulin variant with a human immunoglobulin G (IgG) Fc domain. In this study, we explored the safety and efficacy of BIF in people with type 2 diabetes who had been previously treated with basal insulin. Methods: For this phase 2, 44-site (clinical research centres and hospitals), randomised, open-label, comparator-controlled, 32-week study in the USA, Puerto Rico, and Mexico, we enrolled participants with type 2 diabetes. Eligible participants had to be adults (aged ≥18 years) and to have been treated with basal insulin and up to three oral antidiabetic medicines. Participants were randomly assigned (1:1:1) to subcutaneous administration of BIF (BIF treatment group 1 [BIF-A1] or 2 [BIF-A2]) or insulin degludec. Randomisation was stratified by country, baseline HbA1c values (<8·5% or ≥8·5%; <69·4 or ≥69·4 mmol/mol), use of sulfonylureas (yes or no), and baseline BMI (<30 or ≥30 kg/m 2 ). The randomisation scheme was performed using an interactive web-response system, which ensured balance between treatment groups. Different fasting glucose targets for the BIF-A1 (≤7·8 mmol/L or ≤140 mg/dL; titrated every 2 weeks), BIF-A2 (≤6·7 mmol/L or ≤120 mg/dL; titrated every 4 weeks), and degludec (≤5·6 mmol/L or ≤100 mg/dL) groups were selected. Patients randomly assigned to BIF received a one-time loading dose ranging from 1·5–3 times their calculated weekly dose. The first weekly dose was administered 1 week after the loading dose. We used interstitial fasting glucose measurements from the Dexcom G6 continuous glucose monitoring system to titrate the basal insulin. The primary measure of glycaemic control was change in HbA1c from baseline to week 32 for BIF. BIF was also compared with degludec (with a non-inferiority margin of 0·40%). The efficacy analysis set consisted of data from all randomised study participants who received at least one dose of the study medication and participants were analysed according to the treatment they were assigned. The safety population was the same as the efficacy analysis set. The completed trial is registered at ClinicalTrials.gov (NCT03736785 ). Findings: Between Nov 15, 2018 and Feb 18, 2020, 399 participants were enrolled and randomised to BIF-A1 (n=135), BIF-A2 (n=132), or degludec (n=132); 202 (51%) were female and 197 (49%) were male. 379 were analysed for the primary outcome (BIF-A1: n=130; BIF-A2: n=125; degludec: n=124). Mean HbA1c change from baseline to week 32, the primary outcome, was –0·6% (SE 0·1%) for BIF-A1 and BIF-A2. Degludec achieved a change from baseline of –0·7% (0·1%). The pooled BIF analysis achieved non-inferiority versus degludec for the treatment difference in HbA1c (0·1% [90% CI –0·1 to 0·3]). The hypoglycaemia (≤3·9 mmol/L or ≤70 mg/dL) event rates (hypoglycaemia events per patient per year) in the BIF groups were 25% lower than those in the degludec group (treatment ratio BIF-A1 vs degludec was 0·75 [0·61–0·93]; and BIF-A2 vs degludec was 0·74 [0·58–0·94]). BIF was well tolerated; treatment-emergent adverse events were similar across groups. Interpretation: Weekly BIF achieved a similar efficacy compared with degludec despite higher fasting glucose targets in the BIF groups. Higher fasting glucose targets and lower glucose variability might have contributed to lower hypoglycaemia rates for BIF compared with degludec. These findings support continued development of BIF as a once-weekly insulin treatment for people with diabetes. Funding: Eli Lilly and Company.